Preparation and Antiproliferative Activity Evaluation of Juglone-Loaded BSA Nanoparticles - Ali Jahanban-Esfahlan; Soodabeh Davaran; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2022)
Purpose: Today, the discovery of novel and effective chemotherapeutic compounds is the mainchallenge in cancer therapy. In recent years, the anti-tumoral activity of natural naphthoquinonejuglone (JUG), present in different parts of walnut trees, has received considerable interest. Thepurpose of the current study was to prepare and evaluate the in vitro antiproliferative activity ofJUG-loaded bovine serum albumin nanoparticles (JUG-BSA NPs).Methods: BSA NPs and JUG-BSA NPs were prepared using the desolvation technique. The NPswere characterized for their particle size (PS), zeta potential (ZP), drug loading (DL) capacityand encapsulation efficiency (EE). The anti-proliferative activity of JUG-BSA NPs was evaluatedon A431 and HT29 cancer cell lines using cellular uptake and MTT assays.Results: The PS and ZP values of JUG-BSA NPs were 85 ± 6.55 nm and −29.6 mV, respectively.The DL capacity and EE were 3.7% to 5% and 50.4% to 94.6%, respectively. The cytotoxicityof JUG-BSA NPs was significantly less on both cultured A431 and HT29 cells at the studiedconcentrations when compared to free JUG. However, the effect was not very substantial,particularly at high levels.Conclusion: In conclusion, BSA NPs can be used as a suitable and safe carrier for the deliveryof JUG, a cytotoxic hydrophobic natural compound.